2016
DOI: 10.17712/nsj.2016.2.20150482
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the relationship between amyotrophic lateral sclerosis and susceptibility to serum ferritin level elevation

Abstract: Objective:To study the possible relationship between amyotrophic lateral sclerosis (ALS) patients and their susceptibility to serum ferritin level elevation.Methods:We searched the PubMed, Springer, Medline, and OVID databases for any-language original research articles relating to serum ferritin levels in ALS patients published between June 2005 and June 2015. The search term used with ‘amyotrophic lateral sclerosis’, ‘ferritins’, ‘ferritin’, ‘iron’, ‘iron stores, ‘iron status, ‘iron intake’, and ‘iron consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…It has long been known that in the ALS iron homeostasis is disrupted; there is higher iron in the CSF and spinal cord of ALS patients [137]. While there are a large number of studies that demonstrate elevated levels of serum ferritin in ALS [137,138,139], there is not yet a consensus regarding whether serum ferritin is predictive [139,140,141] or unrelated [137,138] to disease progression and survival rates.…”
Section: Ferritin As a Disease Biomarkermentioning
confidence: 99%
“…It has long been known that in the ALS iron homeostasis is disrupted; there is higher iron in the CSF and spinal cord of ALS patients [137]. While there are a large number of studies that demonstrate elevated levels of serum ferritin in ALS [137,138,139], there is not yet a consensus regarding whether serum ferritin is predictive [139,140,141] or unrelated [137,138] to disease progression and survival rates.…”
Section: Ferritin As a Disease Biomarkermentioning
confidence: 99%
“…With regards to iron, Hozumi et al [44] found ALS patients have higher cerebrospinal fluid iron concentrations. In addition, a very recent meta-analysis including 6 case-control studies found an association between elevated serum ferritin levels and ALS [45]. Exposure to mercury may be linked to the aetiology of ALS [46, 47].…”
Section: Introductionmentioning
confidence: 99%
“…These observations could indicate that microglial Ft upregulation occurs in response to intracellular soluble iron accumulation in SALS spinal cords. A number of recent studies have suggested the relationship between elevated serum levels of Ft, as a candidate biomarker for SALS, and the severity of clinical features of patients with this disease . Thus, elevated serum Ft levels in SALS patients may reflect microglial Ft overexpression in the motor neuron system, although the outlet pathway of Ft from the CNS to the systemic circulation has not yet been clearly identified.…”
Section: Discussionmentioning
confidence: 99%